2011
DOI: 10.1016/j.ejcts.2010.08.048
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of inflow occlusion on the beating heart with cardiopulmonary bypass in the extraction of a mass lesion or a foreign body from the right heart

Abstract: In suitable patient groups, the IOBH technique could be safely performed by experienced centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In comparison, recent studies completed have reported decreased rates of hemodynamic, metabolic, and neurologic complications in dogs undergoing total venous occlusion. 7,9,19 Similar comparisons between cardiopulmonary bypass procedures and inflow occlusion in human medicine have concluded less patient morbidity related to inflow occlusion and a decrease in the use of blood transfusion with this procedure. 9 In addition to these potential patient benefits, the required materials for inflow occlusion are more readily accessible when compared to cardiopulmonary bypass, making its application more realistic for more surgeons.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In comparison, recent studies completed have reported decreased rates of hemodynamic, metabolic, and neurologic complications in dogs undergoing total venous occlusion. 7,9,19 Similar comparisons between cardiopulmonary bypass procedures and inflow occlusion in human medicine have concluded less patient morbidity related to inflow occlusion and a decrease in the use of blood transfusion with this procedure. 9 In addition to these potential patient benefits, the required materials for inflow occlusion are more readily accessible when compared to cardiopulmonary bypass, making its application more realistic for more surgeons.…”
Section: Discussionmentioning
confidence: 92%
“…The principle advantages are the simplicity; the lack of need for specialized equipment; and the minimal cardiopulmonary, metabolic, and hematologic derangements after surgery. 2,9 Limitations of this procedure are related to the brief period of access to the intracardiac structures while performing surgery on a beating heart; a total duration of 4 to 8 min has previously been described for total venous inflow occlusion in dogs. 2 In addition, there is the possibility of significant hemorrhage if the entry incision is not closed swiftly or if there is inadequate occlusion of the azygous or caudal vena cava vessels.…”
Section: Introductionmentioning
confidence: 99%
“…IOBH is a well-known but uncommonly used technique to remove mass lesions and foreign material such as pacemaker leads and catheters from the right atrium 1. In this technique, blood flow from the superior and inferior vena cavae to the right atrium is prevented by occlusion with snares, and the right atrium is then opened.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, this technique is reserved for cases such as pulmonary or aortic valvotomy, cardiac injury, atrial septectomy and extraction of intracardiac thrombus or foreign body 1-3…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Vena caval inflow occlusion (VCIO) is an off-pump technique used in performing brief right-sided open-heart procedures. 5 This technique has been safely used in tricuspid valve vegetectomy. 6 This case series reports the use of VCIO in high-risk cardiac patients with right-sided masses.…”
Section: Introductionmentioning
confidence: 99%